PENGARUH PENGGUNAAN APLIKASI BELANJA ONLINE TERHADAP KEPERCAYAAN KONSUMEN DAN KEPUASAN PEMBELIAN - Shinta Ambar Wati; Wagiyo Wagiyo; Juliono Juliono (STMIK Pringsewu, 2022)
In today's digital era, more and more people who have online shopping applications by using these applications find it helpful and can save time for shopping. The online shopping application is a form of social media designed to make it easier for consumers to shop, although there are various cases of online shopping fraud, such as the quality of goods that do not match the picture, different types of goods, people still use e-commerce to shop online, which where online shopping is inseparable from the relationship of trust between sellers and consumers, as well as the fulfillment of consumer satisfaction. As a formulation of the problem whether the online shopping application has an effect on consumer confidence and purchase satisfaction. This study uses a quantitative descriptive method, as the object is the community of West Pringsewu Village, Environment Six with a sample of 37. Data analysis uses simple linear regression analysis with the help of SPSS version 20 program and conclusions are drawn. As a result of research that there is a positive influence of online shopping applications on consumer confidence and purchase satisfaction. This is evidenced by the t-count X, Y1 of 1.695 t-table 1.689 and t-count X,Y2 of 2.062 t-table 1.689.